Non-Resonant Reaction Rates of 13C(α,n)16O and 22Ne(α,n)25Mg reactions in AGB Stars - Ali, Lana T.; Selman, Ahmed A. (Iraqi Journal of Science, 2021)
Both 13C 16O and 22Ne 25Mg reactions perform a cosmic role in the production of neutrons in AGB stars, which significantly contributes to the nucleosynthesis via the s-process. The astrophysical S-factor for both reactions is calculated in this research, utilizing EMPIRE code and depending on two parameter sets for the optical potential. These datasets were published earlier by McFadden and Satchler (denoted here as MFS) and Avrigeanu and Hodgson (denoted as AH) for the non-resonant region of the spectrum and over a temperature range of . The extrapolated S-factor at zero energy is derived to be and for 13C 16O, while the values were and for 22Ne 25Mg, using MFS and AH parameter sets, respectively, which showed a reasonable agreement with the most recommended value. The differences in the S-factor, S(E), values obtained from these two adopted parameter sets are attributed to the variations of the real potential term’s diffuseness parameter that affects the reaction cross section, hence S-factor, specifically at low energy region. Moreover, the present results imply an influential enhancement of the rates by the electron shielding effect at the low-temperature region in which 13C 16O reaction is activated, especially on 22Ne 25Mg reaction. In addition, for both adopted reactions and overall selected temperature range, the reaction rates using values based on MFS showed acceptable results compared with previous compilations and reference libraries. While the results obtained from AH exceeded all the other compilations even though the resonance contributions are currently unconsidered.